The influence of income tax rate, tunneling incentives, and return on equity on transfer pricing behavior of foreign direct investment enterprises in Vietnam - Tran Quoc Thinh; Nguyen Thi Hai An (Investment Management & Financial Innovations)
The utilization of competitive advantages in international trading has fortuitously put transnational manufacturing enterprises in the position of distorting transfer pricing techniques to maximize profits. The paper aims to explore the influence of the determinants on the transfer pricing behavior of foreign direct investment enterprises in Vietnam. The paper collects primary data from the financial statements of 96 foreign direct investment enterprises in Vietnam over six years from 2016 to 2021. The paper gets a final panel data of 576 observations to be processed by the fixed effects model estimation method using EViews 12. Supporting agency theory and positive accounting theory, the results show that the income tax rate negatively influences transfer pricing behavior, while tunneling incentives and return on equity positively affect transfer pricing behavior. The paper highlights that government agencies should reperform and implement fiscal policies synchronously to be able to monitor transfer pricing behaviors of foreign direct investment enterprises in Vietnam.